Comparative study on the effect of different rubber waste as filler on recycled PVC - Kee, Yee Hang (2024)
The rising amount of rubber waste and the usage of polyvinyl chloride (PVC) has contributed to severe environmental issues, which can be tackled by recycling rubber waste and PVC into value-added products. This research aims to develop a new composite using recycled PVC (rPVC) from carpet backing material with different types of rubber waste, known as Almost Like Unvulcanized Material (ALUM), which is an industrial rubber scrap, and cryogenically grounded waste tire powder (LeHigh) for car floor mat application. Composites containing rPVC and different loading of ALUM and LeHigh ranging from 0 to 30 wt% have been produced through melt mixing using a Brabender internal mixer at a temperature of 165 ℃. The rubber particles were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Particle Size Analysis (PSA), Thermogravimetric Analysis (TGA) and Scanning Electron Microscopy (SEM) to evaluate their functional groups, particle size distribution, thermal stability and surface morphology, respectively. Besides that, the effect of different rubber waste on the characteristics and properties of rPVC composites has been evaluated through FTIR, TGA, SEM, processing torque, tensile test, swelling absorption and hardness test. FTIR analysis confirmed that there was no chemical interaction between rPVC and the rubber particles. Addition of ALUM showed a reduction in the thermal stability, whereas LeHigh showed increasing thermal stability of rPVC composites. The melt mixing of rPVC also becomes harder when increasing both ALUM and LeHigh loadings, as depicted by the increased processing torque caused by the stiffening of the composite system. Furthermore, the tensile strength, elongation at break and water absorption of the rPVC composites have been reduced, whereas the elastic modulus and hardness were improved by increasing both the filler loading. The SEM morphological study of the tensile fractured surface revealed that both ALUM and LeHigh particles have fairly good dispersion in rPVC at low filler loading. However, the dispersion and interfacial interaction of rubber particles with rPVC become weaker with increasing filler loading up to 30 wt%, leading to reduced tensile strength. The evaluation of the suitability of both ALUM/rPVC and LeHigh/rPVC for car floor mat application was carried out. The standard specification values desired to produce a car floor mat include a minimum tensile strength of 5 MPa, minimum elongation at break of 25 %, maximum water absorption of 2.5 % and Shore A hardness of 90 ± 5. Upon evaluation, the optimum loading of ALUM and LeHigh in rPVC suitable for car floor mat application is 10 wt% and 20 wt%, respectively, to produce a composite with properties fulfilling the standard specification values. However, by comparing both the rubber particles, Lehigh is more preferred and suitable to be used as filler in rPVC to produce the car floor mat as compared to ALUM. LeHigh can be added up to 20 wt% as compared to only 10 wt% of ALUM in rPVC, and the smaller particle size of LeHigh could produce a better adhesion to rPVC matrix to provide a better overall property as desired for the car floor mat application